1960
DOI: 10.1042/bj0740501
|View full text |Cite
|
Sign up to set email alerts
|

The isolation and properties of a proteolytic enzyme, cathepsin D, from bovine spleen

Abstract: HAEM-PROTEIN REDUCTION BY COLOROPLASTS 501 to the conclusion that the factor can catalyse the reduction of soluble material in the leaf extracts. Further work is necessary to trace the paths of hydrogen transport after the reduction of the factor by the illuminated chloroplast and to determine the nature of the group concerned in the oxidation-reduction cycle. SUMMARY 1. A protein factor from leaves, previously shown to be active in catalysing the reduction of methaemoglobin and metmyoglobin by illuminated chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
2
5

Year Published

1962
1962
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(67 citation statements)
references
References 25 publications
2
58
2
5
Order By: Relevance
“…Yet, albumin is a substrate more specific for cathepsin E, and globin for cathepsin D [62][63][64] (Table 8). Figure 9.…”
Section: Determination Of Activity and Concentrationmentioning
confidence: 99%
“…Yet, albumin is a substrate more specific for cathepsin E, and globin for cathepsin D [62][63][64] (Table 8). Figure 9.…”
Section: Determination Of Activity and Concentrationmentioning
confidence: 99%
“…The major acid proteinase, now called cathepsin D, was studied by Anson (1939) and other acid peptidases of the bovine spleen were characterized by Fruton and coworkers (Tallan et al, 1952). The interest of immunologists in the processing ofprotein immunogens in the spleen led to further work on cathepsin D (Lapresle & Webb, 1960;Press et al, 1960), and also to the studies of Zff and co-workers LoSpalluto et al, 1970) on the degradation of immunoglobulins by human spleen enzymes at both acid and neutral pH values. The purpose of the present study was to purify and characterize the enzymes responsible for the neutral proteinase activity of human spleen.…”
mentioning
confidence: 99%
“…In contrast to above mentioned studies seven to eight cleavage sites in porcine //-lipotropin have been reported by Akopyan and colleagues who used a cathepsin D Barfit et al (1979), the data have been reconsidered in view of the revised human fl-lipotropin structure (see Fig. 2); (C) Gr~f et al (1979b), Benuck et al (1978b), Burbach et al (1980b); (D) Lebouille and Burbach (unpublished); (E) Press et al (1960).…”
Section: Cathepsin Dmentioning
confidence: 93%